Analisis proksimat, asam lemak dan asam amino pada pangan tradisional ikan lemuru dengan proses pengeringan berbeda [Proximate analysis, fatty acids and amino acids of lemuru fish traditional foods with variation of drying processes] - Ni Made Ayu Suardani Singapurwa (Jurnal Teknologi & Industri Hasil Pertanian, 2023)
Lemuru fish need preservation because it is easily damaged and only produced seasonally. Apart from its nutritional value as a source of essential protein to humans, lemuru fish is very cheap. Generally, the people of Jembrana Regency in Bali preserve it by processing it into seasoned dried fish known as “Pedetan”.  Research  carried out oven drying, sun drying, and direct sunlight to determine the best method for drying lemuru fish with and without spices. Results showed that the drying method had significant effects on proximate contents of lemuru fish. The lowest moisture content (7.31%) was obtained in the treatment of seasoned lemuru fish with oven drying. Oven-dried unseasoned fish had the highest protein content of 67.69%, while sun-dried fish, both seasoned and unseasoned samples, had the highest fat content with an average of 13.30%. The highest saturated fatty acid was palmitic acid, and the highest unsaturated fatty acid was cis-9 oleic acid. Meanwhile, the highest  amino acid was the L-glutamic acid.